Synthesis and characterization of polyurethane-based self-luminous pavement coatings: a performance evaluation study - Lu, Qinghe; Liu, Xiajun; Lu, Zhen; Li, Ke (Frontiers in Materials, 2024)
Improving drivers' nighttime sight is essential given the growing development of urban transportation. In this study, polyurethane-based self-luminous pavement coating (PSC) was prepared by doping luminous powder (LP) into polyurethane materials. The superior optical properties and chemical stability of the coating were ensured by synthesizing the polyurethane-based material. Then, the PSC was evaluated for its comprehensive performance, such as luminescence performance, aging resistance, and abrasion resistance, by using a variety of characterization methods, including fluorescence spectral analysis, Fourier transform infrared spectroscopy, fluorescence microscope imaging, and mechanical property testing. The results show that the 50-mesh LP has the optimal overall performance, with an initial luminescence that exceeds that of 100 and 400 mesh. The initial brightness of PSC is mainly influenced by LP, which increases with the dosage. The lattice structure and luminescent properties of the luminescent material did not change after the preparation of the coating. The peak excitation wavelength of 420 nm means that the coating has the best excitation effect in UV light. The primer marking coating can effectively improve the abrasion resistance of PSC. and the mass loss of PSC with a coating thickness of 0.4 kg/m 2 is 52.9% of that without primer marking coating, and the optimal coating thickness is 0.6 kg/m 2 . This research provides an innovative solution to improve nighttime roadway lighting, which provides useful support for the sustainable development of urban transportation infrastructure and the construction of intelligent transportation systems.